Penerapan Metode Kolase dalam Meningkatkan Kreativitas Siswa di Sanggar Bimbingan Aisyiyah Kampung Pandan Malaysia - Triwahyuningsih, Dewi Fatimah; Armitha Armitha; Rahmawati, Riska Dewi; Maryam, Andi (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
This community service activity aims to improve students' creativity at Sanggar Bimbingan Aisyiyah (SBA) Kampung Pandan, Malaysia, through the application of the collage method. The method used in this activity is participatory, involving 27 students from grades 2 to 5 in a series of workshops and direct practice. The results of the community service show that the collage method is effective in improving students' creativity, which is characterized by increased fine motor skills, logical thinking skills, and imagination and experimentation in creating works of art. Of the 10 students sampled, 5 students showed "Very Developed" creativity development, 4 students "Quite Developed," and 2 students "Not Yet Developed," with an average creativity score reaching 80. This activity concludes that the application of the collage method can be an effective community service strategy in improving children's creativity in non-formal educational environments and is recommended to continue to be implemented at SBA Kampung Pandan.